Protective and pro-inflammatory roles of intestinal bacteria. Issue 2 (June 2016) - Reinoso Webb, Cynthia; Koboziev, Iurii; Furr, Kathryn L.; Grisham, Matthew B.
Abstract: The intestinal mucosal surface in all vertebrates is exposed to enormous numbers of microorganisms that include bacteria, archaea, fungi and viruses. Coexistence of the host with the gut microbiota represents an active and mutually beneficial relationship that helps to shape the mucosal and systemic immune systems of both mammals and teleosts (ray-finned fish). Due to the potential for enteric microorganisms to invade intestinal tissue and induce local and/or systemic inflammation, the mucosal immune system has developed a number of protective mechanisms that allow the host to mount an appropriate immune response to invading bacteria, while limiting bystander tissue injury associated with these immune responses. Failure to properly regulate mucosal immunity is thought to be responsible for the development of chronic intestinal inflammation. The objective of this review is to present our current understanding of the role that intestinal bacteria play in vertebrate health and disease. While our primary focus will be humans and mice, we also present the new and exciting comparative studies being performed in zebrafish to model host–microbe interactions.